# Extension of the additive Cauchy functional equation

Let $f\colon (0,\alpha)\to \def\R{\mathbf R}\R$ satisfy $f(x + y)=f(x)+f(y)$ for all $x,y,x + y \in (0,\alpha)$, where $\alpha$ is a positive real number. Show that there exists an additive function $A \colon \R \to \R$ such that $A(x) = f(x)$ for all $x \in (0, \alpha)$. Simply I want to define a function A In specific form as an extension of the function f wich is additive functional equation. I tried to define the function A .

• Welcome to math.SE! This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level. – Pedro Apr 2 '15 at 10:55

Let $x > 0$. Choose $n \in \def\N{\mathbf N}\N$ with $\frac xn < \alpha$. Define $A(x) := nf(\frac xn)$. Note that this is well-defnined: If $m\in \N$ is another natural number such that $\frac xm < \alpha$, we have \begin{align*} mf\left(\frac xm\right) &= mf\left(\sum_{k=1}^n \frac x{mn}\right)\\ &= m\sum_{k=1}^n f\left(\frac x{mn}\right)\\ &= \sum_{l=1}^m n f\left(\frac x{mn}\right)\\ &= nf\left(\sum_{l=1}^m \frac x{mn}\right)\\ &= nf\left(\frac x{n}\right). \end{align*} For $x < 0$ choose $n \in \N$ with $\frac xn > -\alpha$ and define $A(x) := -nf(-\frac xn)$, finally, let $A(0) = 0$. Then $A$ is an extension of $f$, to show that it is additive, let $x,y \in \def\R{\mathbf R}\R$. Choose $n \in \N$ such that $\frac xn, \frac yn, \frac{x+y}n \in (-\alpha, \alpha)$. We have if $x,y \ge 0$: \begin{align*} A(x+y) &= nf\left(\frac{x+y}n\right)\\ &= nf\left(\frac xn\right) + nf\left(\frac yn\right)\\ &= A(x) + A(y) \end{align*} If both $x,y \le 0$, we argue along the same lines. Now suppose $x \ge 0$, $y \le 0$, $x+y \ge 0$. We have $A(y) = -A(-y)$ be definition of $A$. Hence \begin{align*} -A(y) + A(x+y) &= A(-y) + A(x+y)\\ &= A(-y+x+y)\\ &= A(x). \end{align*} If $x \ge 0$, $y \le 0$, $x+y \le 0$, we have $-x \le 0$ and \begin{align*} -A(x) + A(x+y) &= A(-x) + A(x+y)\\ &= A(y) \end{align*}